2003
DOI: 10.1176/appi.ajp.160.5.873
|View full text |Cite
|
Sign up to set email alerts
|

Lower Concentration of Hippocampal N-Acetylaspartate in Familial Bipolar I Disorder

Abstract: This preliminary study provides support for the existence of neuronal loss, neuronal metabolic dysfunction, or interneuronal neuropil reduction in the hippocampal region in male patients with familial bipolar I disorder. The finding of normal hippocampal choline levels in these patients does not provide support for ongoing myelin breakdown or glial cell proliferation in this brain region in familial bipolar I disorder. The significant association between illness duration and N-acetylaspartate concentration in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
77
0
10

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(93 citation statements)
references
References 84 publications
5
77
0
10
Order By: Relevance
“…This would suggest that Cr may not be a stable resonance to be used as an internal standard or reference ratio in bipolar depression research. This certainly warrants further investigation as the current literature in bipolar disorder, although different in methodology, mood state, and brain region, has reported increased creatine (Deicken et al, 2001;Michael et al, 2003Ftrend, Hamakawa et al, 1999Fmen only), decreased creatine (Deicken et al, 2003), or no change in creatine (Hamakawa et al, 1998;Friedman et al, 2004;Cecil et al, 2002;Brambilla et al, 2005;Frey et al, 2005).…”
Section: Discussionmentioning
confidence: 87%
“…This would suggest that Cr may not be a stable resonance to be used as an internal standard or reference ratio in bipolar depression research. This certainly warrants further investigation as the current literature in bipolar disorder, although different in methodology, mood state, and brain region, has reported increased creatine (Deicken et al, 2001;Michael et al, 2003Ftrend, Hamakawa et al, 1999Fmen only), decreased creatine (Deicken et al, 2003), or no change in creatine (Hamakawa et al, 1998;Friedman et al, 2004;Cecil et al, 2002;Brambilla et al, 2005;Frey et al, 2005).…”
Section: Discussionmentioning
confidence: 87%
“…11 Recently, magnetic resonance spectroscopy (MRS) has also provided evidence for hippocampal neurometabolite alterations in bipolar disorder. [12][13][14] After 50 years of clinical use, lithium salts have remained the most effective and widely used longterm preventive treatment for bipolar disorder to date. 15,16 Lithium robustly upregulates the neuroprotective protein BCL2 on the outer mitochondrial membrane and confers neuroprotection in a model of transient focal cerebral ischemia in rats.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 In healthy individuals, NAA is present in the brain at concentrations of 8-10 mmol/l, 4 and thus follows glutamate as the second most abundant amino acid in the central nervous system. 5 After early research with rat brain mitochondria suggested that NAA is of mitochondrial origin, 6 Truckenmiller et al 7 demonstrated that NAA is synthesized in mitochondria by the membrane-bound enzyme L-aspartate N-acetyltransferase, a catalyst that is found only in the brain ( Figure 2). Further studies also indicated that the synthesis of NAA is energy dependent, and stimulated by adenosine diphosphate (ADP).…”
mentioning
confidence: 99%
“…7,14,17 When taken together, these studies suggest that NAA levels are closely related to mitochondrial energy metabolism, and thus may serve as a measure of mitochondrial function. 8,17,18 A number of 1 H MRS studies have demonstrated reduced NAA levels in patients with bipolar disorder compared to normal controls 2,5,[19][20][21] (Table 1). Although the use of Cr as a reference peak has been criticized due to observations of alterations in this signal following treatment with lithium and/or sodium valproate, 22 findings of decreased NAA/ Cr þ PCr ratios in bipolar subjects have been corroborated by observations of similarly significant reductions in NAA levels measured relative to voxel H 2 O levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation